Preliminary Memorandum on the Fourth Five-Year Plan Mysore State - Planning Commission (Planning Commission, 1958)
Democratic planning in India has been from the beginning, an intensely purposive socioeconomic Activity directed towards the attainment of the ideals enshrined in the Constitution. Although harmonious evolution is of the essence of the planning process, there arc periods which are designed to constitute a phase of far-reaching significance in the economic life of the country. One such phase spans the years from 1961 to 1976.- In these 15 years is sought to be achieved a degree of progress which, if the economy were to arrow without any external stimuli, would take decades. This deliberate concentration of economic activity makes the tasks in each Plan period exceedingly arduous and the difficulties are further accentuated if, during the previous Plan period, performance in any sector of the economy falls short of expectations.
Government of Mysore
Government of Mysore Planning, Housing and Social Welfare Department
Keywords: Size and Pattern of Investment; Financial Resources for the Plan as at Present Estimated; 1966 A Prospective View; Employment; Sectoral Programmes; District and Block Plans; Backward Areas; Strengthening of Administration and Machinery for Planning; Approach; Objectives Outlay and Priorities; fundamental task of planning; Construction Employment